Exploring the electrocatalytic activity of cobalt disulfide nanosheets towards the hydrogen evolution reaction with in situ ECAFM. Issue 16 (23rd July 2021) - Dong, Yan; Sun, Hui; Liu, Guangyi
Abstract : CoS2 nanosheets exhibited a remarkable electrocatalytic activity towards the HER in acidic and alkaline electrolytes. Abstract : Exploring an efficient and durable electrocatalyst for the hydrogen evolution reaction (HER) is vitally necessary for sustainable energy conversion and storage systems. Herein, we fabricated CoS2 nanosheets through a one-step hydrothermal reaction and investigated their electrocatalytic performance towards the HER in acidic and alkaline electrolytes. With sodium ethyl xanthate (SEXT) and cobalt acetate tetrahydrate as S and Co sources, the CoS2 nanosheets were hydrothermally prepared under 200 °C for 10 hours. The CoS2 -2 nanosheets synthesized from a 7.5 atomic proportion of S to Co exhibited a remarkable electrocatalytic activity towards the HER with an overpotential of ∼145 mV in 0.5 M H2 SO4 solution and 288.5 mV in 1 M KOH solution at 10 mA cm −2, respectively. And after 2000 cycles, their current density remained almost constant. FESEM, TEM, AFM, and XRD showed that CoS2 -2 nanosheets possessed a good crystallinity and small size, facilitating sufficient exposure of electrocatalytically active sites. In situ electrochemical atomic force microscopy (ECAFM) demonstrated that after the HER, the morphology of individual CoS2 -2 nanosheets had no obvious change in acidic solutions and transformed significantly in alkaline media, while their height, width and area distinctly increased in both acidic and alkaline media. Nevertheless, the overall morphology of CoS2 -2 cuboids (aggregates) as-observed by FESEM hardly changed during the HER, confirming their excellent HER stability. The different change for atomic proportion and binding energy of Co 3+ and Co 2+ indicated that the electrocatalytic mechanism of CoS2 -2 towards the HER in acidic electrolytes was different from that in alkaline media.